Translation Strategies Used In Jasa Burung Pipit And Its Translation The Good Deed Of The Sparrow - Dewi Wulan Sari (Asosiasi Dosen Muda Indonesia, 2023)
Translation is the process of transferring the meaning from the source language to the target language. The objective of this research is to find out the translation strategies found in Jasa Burung Pipit and its translation The Good Deed of The Sparrow. This research used qualitative research method. The theory used is the translation strategies form Chesterman. The result showed that there are 6 translation strategies were found. They are literal translation (18 data), loan, calque (2 data), clause structure change (1 data), cohesion change (3 data), synonymy (6 data) and distribution change (12 data). Based on the data collected, literal translation strategy is the most dominant translation strategy used.